Nomenclatural review and history of Pycnoporus (Polyporaceae): A widespread, bright-reddish genus in Basidiomycota - Araújo F. Gurgel, Rafaela; S. Carvalho, Catarina; K. Ishikawa, Noemia; Cabral, Tiara S. (Phytotaxa, 2023)
N/A